2012
DOI: 10.1016/j.bbmt.2012.01.006
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Thymic Reconstitution Following Bone Marrow Transplantation in Neonatal Mice is VEGF-Dependent

Abstract: Age-related differences in thymic function influence the rapidity of T cell reconstitution following hematopoietic stem cell transplantation (HSCT). In adults, thymic reconstitution is delayed until after marrow engraftment is established, and is significantly improved by approaches that increase marrow chimerism, such as pre-transplant irradiation. In contrast, we show that neonatal mice undergo more rapid and efficient thymic reconstitution than adults, even when bone marrow engraftment is minimal and in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…Although the role of ECs during tissue regeneration has traditionally been attributed to their role in vascularization, including in the thymus (25), recent work has suggested that ECs can also contribute towards regeneration via their production of so-called angiocrine factors (2628). Using a technique to constitutively activate the Akt pathway in ECs using the prosurvival adenoviral gene E4ORF1 (29), ECs can be propagated and expanded ex vivo (exEC) while maintaining their phenotype and vascular tube formation capacity (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although the role of ECs during tissue regeneration has traditionally been attributed to their role in vascularization, including in the thymus (25), recent work has suggested that ECs can also contribute towards regeneration via their production of so-called angiocrine factors (2628). Using a technique to constitutively activate the Akt pathway in ECs using the prosurvival adenoviral gene E4ORF1 (29), ECs can be propagated and expanded ex vivo (exEC) while maintaining their phenotype and vascular tube formation capacity (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…These include IL-7, CXCL12, SCF, CCL25, and the notch ligand DLL4. In fact, many of these have been identified as part of the mechanistic pathways for exogenous thymic regeneration through such systemic means as sex steroid ablation, which crucially needs IL-7 (but not KGF) to mediate regeneration (76), and induces expression of the Notch ligand Dll4 (36), CCL25, which induces importation of progenitors (35), and VEGF, which promotes vascularization and endothelial cell function and is also likely involved in endogenous thymic regeneration (77, 78). …”
Section: Endogenous Thymic Regenerationmentioning
confidence: 99%
“…We have tested to determine whether in vitro-derived progenitors are capable of thymus settling in adult mice, and we observed a low frequency of mice with thymus engraftment (data not shown). The precise reasons for the difference in engraftment between the neonatal and the adult is unknown, however, the increase in the neonatal vasculature compared with adults, 43 severe thymus involution and continued atrophy in adult NSG mice may be factors influencing human proT-cell engraftment in neonatal vs adult mice.…”
Section: Blood 19 December 2013 X Volume 122 Number 26 In Vitro Promentioning
confidence: 99%